Perancangan Sistem Ukuran Overall Equipment Effectiveness untuk Memonitor dan Memperbaiki Efisiensi Proses di Bagian Filling dan Packing - Yuni Fitria Sari; Wahyudi Sutopo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
In the most general sense, OEE (Overall Equipment Effectiveness) can be described as a universally accepted set of metrics that bring clear focus to the key success drivers for manufacturing enterprises. In this case, OEE quantifies how well a Filling and Packing Unit (F & P Unit) performs relative to its designed capacity, during the periods when it is scheduled to run. OEE breaks the performance of a F & P Unit into three separate but measurable components: Availability, Performance, and Quality. Each component points to an aspect of the process that can be targeted for improvement as parts of Total Productive Maintenance (TPM). In a TPM program, the Teams at F & D Unit, should looking to see what causes the problems so that they know when it is time to act, and know what problem needs to be fixed. The Cause Effect Diagram used on identify the root causes of poor equipment performance, then Multiple Linear Regression (MLR) used to generate the relationship of components causes of poor equipment performance and then to improve equipment operation. The OEE rating is targeted 85%, butit is unlikely that F & P Unit only can run at 78.2% rating. A comprehensive, The Design of Overall Equipment Effectiveness Metrics System, will provide operator’s F & P Unit to monitor and improve the efficiency of process of manufacturing.